2017
DOI: 10.17219/acem/68292
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose computed tomography in assessment of pulmonary abnormalities in children with febrile neutropenia suffering from malignant diseases

Abstract: Background. Management of febrile neutropenia in pediatric patients is challenging. Chest X-ray and CT scan help to identify infective foci; however, exposure to radiation is a risk factor for development of secondary cancer. For this reason, attention is paid to reducing radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…In patients with clinical signs and symptoms of pneumonia radiographic imaging (conventional chest X-ray radiography (CXR) or chest CT scan) is recommended and should be obtained within 24 h. In one study, sensitivity, specificity, positive predictive value, and negative predictive value for conventional radiography were 36%, 93%, 50% and 88%, and for low-dose CT scan 73%, 91%, 62%, and 94%, respectively [ 127 ]. Therefore, chest CT scan is the preferred modality owing to the higher sensitivity and specificity [ 127 , 128 ]. The optimal timing of radiological imaging is not known; in studies and in clinical practice, CXR or chest CT scan is often performed within 24 h [ 127 , 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with clinical signs and symptoms of pneumonia radiographic imaging (conventional chest X-ray radiography (CXR) or chest CT scan) is recommended and should be obtained within 24 h. In one study, sensitivity, specificity, positive predictive value, and negative predictive value for conventional radiography were 36%, 93%, 50% and 88%, and for low-dose CT scan 73%, 91%, 62%, and 94%, respectively [ 127 ]. Therefore, chest CT scan is the preferred modality owing to the higher sensitivity and specificity [ 127 , 128 ]. The optimal timing of radiological imaging is not known; in studies and in clinical practice, CXR or chest CT scan is often performed within 24 h [ 127 , 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…A MEDLINE search was performed, using the following terms: "CT scan hematological malignancy pulmonary infection", "CT scan pulmonary aspergillosis stem cell transplantation", "CT scan pulmonary aspergillosis hematopoietic stem cell transplantation", "CT scan pulmonary aspergillosis bone marrow transplantation", to identify CT scan findings helpful in defining infectious etiological diagnosis of pneumonia in HM-HSCT patients. A total of 22 studies were identified [11][12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], 13 of them [4,[11][12][13][14][15]19,21,24,[35][36][37][38] specifically describing different radiological findings in pediatric patients with fungal, bacterial and viral pneumonia.…”
Section: Image Analysismentioning
confidence: 99%
“…U njih 116 (84,06 %) detektirali su ground-glass zamućenja (n = 79), nodule (n = 60) i zračno-bronhogramske konsolidacije (n = 58). Nadalje, kod njih 94 (81,03 %) točno su dijagnosticirali upalne infiltrate 45 . Sun i sur.…”
Section: Ldct Pregledi Torakalnih Organaunclassified